PENDUGAAN PARAMETER GENETIK BEBERAPAKARAKTER AGRONOMI PADA POPULASI TANAMAN TOMAT (Lycopersicum Esculentum MILL.) - Saiful Bahri; Elza Zuhry; Deviona ' (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2015)
The objective of this research was to estimate genetic parameters such as variability, heritability, various agronomic characters in tomato population through crossbreeding FI. Research was arranged experimentally using Randomized Block Design (RBD) consists of 13 tomato genotypes from crosses with 3 replications were placed haphazardly. Seedlings were transplanted to a plot with a size of 1 m x 5 m with a spacing of 50 cm x 50 centimeter. Each plot treatment plant sample taken as many as 10 plants of 20 tomato plants for plant height, stalk diameter, weight per fruit, fruit length, thick fruit pulp, fruit diameter, total fruit number per plant and total fruit weight per plant. Analysis of variation was later translated into genetic parameters with Griffing method IV models. The outcomes indicated that the genotype of Champions can be chosen as one of the hybrid parents because it delivers a sound value to improve the character of days to flowering, stem diameter, harvesting, thick fruit pulp, fruit diameter, weight per fruit, and total fruit weight per plant. Genotype T78x1, T13x1, T3x13 and T1x13 has a value corresponding to improve the role of stem diameter, days to flowering, and weight per fruit. Characters that have a high heritability with criteria that plant height, flower age, harvesting, planting fruit weight, number of fruits per plant, weight per fruit, fruit number and length of the cavity are positively correlated with total fruit weight per plant. Keyword: Breeding tomatoes, diversity, variability and heritability